Lesotho CAADP bienniel review brief: Africa agriculture scorecard performance and lessons - Khesa, M.; Nhemachena, Charles; Matchaya, Greenwell C.; Nhlengethwa, Sibusiso (International Food Policy Research Institute, 2019)
This brief summarizes the performance, key issues, and recommendations for Lesotho from the inaugural BR report to help improve and strengthen the country’s efforts to domesticate and implement the commitments of the Malabo Declaration within its own national agricultural investment plan and strategy.